Negative Impact of Gene Therapy on Melanoma Disease - Nadhea Aurel Zalfanisa Inzagi; Nadia Azhar Samasta; Dewi Ghitsatul Ala; Ibrahim Bin Said (Yayasan Adra Karima Hubbi, 2024)
The incidence of melanoma is rapidly increasing worldwide, posing a significant public health problem. Gene therapy for treating diseases has been discovered since 1989. Research developments to make gene therapy an effective treatment method are ongoing. Primary extracutaneous melanoma can be ocular, gastrointestinal, mucosal, leptomeningeal, genitourinary, and lymphatic. The relationship between ultraviolet (UV) exposure and the development of melanoma is highly acute and complex, and intermittent sun exposure significantly increases the risk of melanoma. It is the fifth most common type of cancer in men and the sixth in women. Mucosal melanoma is a rare disease that differs from melanoma arising elsewhere in the body. Although melanocytes are most abundant in the skin, they can also be found in smaller numbers in mucous membranes and the eyes. There are epidemiological, genetic, and physiological differences between melanomas arising from melanocytes in these various locations, and these differences have important implications for both disease prognosis and treatment.